The Debt Crisis and the Future of International Bank Lending - Heller, H. Robert (American Economic Review, 1987)
As we approach 1987, the Gordian knot of the international debt problem seems to be tightening again. Rescheduling agreements and requests for new money by several important countries are on the agenda. It will take farsighted and strategic thinking on behalf of all participants to overcome the mounting problems confronting us. Nevertheless, I firmly believe that the problems will continue to be manageable if all participants focus on their long-term interest in coming to a satisfactory solution. It is within that general framework that I would like to approach the topic of this paper. The role of the banks in the debt crisis cannot be seen in isolation. Important interdependences must be considered, including the responsibilities of the debtor countries, the industrialized countries, and the international agencies.